Association of germline rare pathogenic mutations in guideline‐recommended genes with prostate cancer progression: A meta‐analysis. Issue 1 (21st October 2021) - Shi, Zhuqing; Lu, Lucy; Resurreccion, William Kyle; Yang, Wancai; Wei, Jun; Wang, Qiang; Engelmann, Valentina; Zheng, Siqun Lilly; Cooney, Kathleen A.; Isaacs, William B.; Helfand, Brian T.; Lu, Jim; et al.
Abstract: Background: Germline mutations in several genes, mainly DNA repair genes, have been associated with prostate cancer (PCa) progression. However, primarily due to the rarity of mutations, statistical evidence for these associations is not consistently established. The objective of this study is to synthesize evidence from multiple studies using a meta‐analysis. Methods: Genes analyzed were chosen based on National Comprehensive Cancer Network guidelines recommendations (10 genes) and a commonly reported gene ( NBN ). PCa progression in this analysis was defined as either having metastases or PCa‐specific mortality. We searched PubMed for papers published before April 26, 2021, using selected keywords. Pooled odds ratio (OR) was estimated in all races and Caucasians‐only using both fixed‐ and random‐effect models. Results: The search identified 1028 papers and an additional five from a manual review of references. After a manual process that excluded noneligible studies, 11 papers remained, including a total of 3944 progressors and 20, 054 nonprogressors. Combining results from these eligible studies, mutation carrier rates were significantly higher in progressors than nonprogressors for NBN, BRCA2, ATM (under both fixed‐ and random‐effect models), for CHEK2 (under fixed‐effect model only), and for PALB2 (under random‐effect model only), p < 0.05. Pooled OR (95% confidence interval) was 6.38 (2.25–18.05), 3.41 (2.31; 5.03), 1.93 (1.17–3.20), and 1.53 (1.00–2.33) for NBN, BRCA2, ATM, and CHEK2, respectively, under fixed‐effect model and 2.63 (1.12–6.13) for PALB2 under random‐effect model. No significant association was found for the six remaining genes. Certainty of evidence was low for many genes due primarily to the limited number of eligible studies and mutation carriers. Conclusions: Statistical evidence for five genes was obtained in this first meta‐analysis of germline mutations and PCa progression. While these results may help urologists and genetic counselors interpret germline testing results for PCa progression, more original studies are needed.